“SER” AND “ESTAR” VERBS: PERMANENT-TEMPORARY CONTINUUM AND PORTUGUESE AS A FOREIGN LANGUAGE TEACHING (Muitas Vozes, 2021)
The aim of this paper is to present a proposal of teaching-learning material of the "ser" and "estar" (‘to be’) verbs for using with students of Portuguese as a Foreign Language (PFL). The objective is to present the [+ permanent] - [+ temporary] continuum, having as reference the counterpoint between the prescription of normative grammars and the current uses of language in interactional contexts. The theoretical framework adopted is Use-Centered Linguistics, for which language is a complex adaptive system, a fluid structure, constituted, simultaneously, of more or less regular patterns and patterns in permanent emergence, governed by cognitive and/or communicative needs (BYBEE, 2010). Grammar is seen as a sociocultural phenomenon; its structure and its regularity are originated in the discourse and shaped in a continuous process; mastering it means not only mastering mechanisms of a morphosyntactic nature, but also processes associated with textual organization and interactional phenomena, which involve linguistic and cognitive aspects. Huback's (2011) work on these verbs in the teaching of PFL will also be used. The methodology consists of observing occurrences of the use of these verbs in various texts and organizing them in a continuum that reflects the notions of permanence/temporality that constitute them.